Pengaruh Penggunaan Dompet Digital Gopay terhadap Perilaku Konsumtif Wisatawan di Cirebon - Yanthi Setyawati; Ade Firdiana; Ferdiana Ferdiana; Tri Erie Wardhani; Itat Tatmimah (Yayasan Literasi Sains Indonesia, 2025)
The rapid growth of digital technology has transformed the way people conduct economic transactions, including in the tourism sector. The convenience of using digital wallets such as GoPay has influenced tourists’ consumption patterns, making transactions faster and more practical. This study aims to analyze the effect of GoPay usage on the consumptive behavior of tourists in Cirebon. The research applied a quantitative approach using a survey method on tourists who used GoPay during their visits. The research instruments were tested for validity and reliability, and data were analyzed through simple linear regression. The results revealed that GoPay usage has a positive and significant influence on tourists’ consumptive behavior. Higher usage intensity of GoPay tends to increase impulsive buying and excessive spending among tourists. These findings indicate that the ease of use and promotional offers provided by GoPay play an important role in shaping tourists’ consumption behavior in the digital era. The study concludes that improving digital financial literacy among tourists is crucial to ensure responsible and balanced use of e-wallets. It is also recommended that digital payment providers and tourism stakeholders collaborate to develop a payment ecosystem that promotes both efficiency and sustainable consumer behavior.